Eight silly monkeys - Haskamp, Steve (Los Angeles, California : Piggy Toes Press, 2003)
Eight monkeys jump on the bed, falling off and bumping their heads one at a time.
On board pages with die-cut holes.
Keywords: Counting-out rhymes -- Juvenile fiction